(untitled) (Jagannath University Journal of Life and Earth Sciences, 2025)
Technological advancements have facilitated increased access to the internet, leading to widespread cyberloafing.As cyberloafing becomes more prevalent, organizations are concerned about its potential to disrupt productivity and compromise security. In the context of employees from private and government banks in Dhaka city, this research aims to delve into how perceptions of organizational fairness impact cyberloafing, with an emphasis on the mediating effect of work engagement.A cross-sectional survey was conducted with 400 participants using adapted and validated Bangla versions of scales measuring organizational justice, cyberloafingbehaviors, and work engagement. The hypotheses were tested through multiple statistical analyses, including regression and mediation models. The findings revealed a significant negative relationship between organizational justice and cyberloafing, indicating that higher perceptions of fairness are associated with reduced cyberloafingbehavior. Organizational justice was also found to positively influence work engagement. Furthermore, work engagement partially mediated the relationship between organizational justice and cyberloafing. The study also found significant associations between demographic variables (such as age, education, salary, experience, and social media use) and cyberloafingbehavior. The findings highlight the importance of fostering fairness and engagement in the workplace to reduce cyberloafing and support greater employee productivity and job-related satisfaction. Jagannath University Journal of Life and Earth Sciences, 10(1) 17-23